Implementasi Program Literasi di sekolah Dasar terhadap Minat Baca Siswa di SDN 66/IV Kota Jambi - Nuranisa, Dedek; Sari, Diana Ayu Puspita; Bastian, Oktavioni; Rosdianah, Puput Tri; Sulistia, Vina (Lembaga Yasin AlSys, 2022)
This research was motivated by the existence of a school literacy movement program that was launched by the ministry of education and culture in 2015. This movement has three (3) stages, namely habituation, development, and learning. At SDN 66/IV Jambi City, literacy habituation activities have been carried out every Thursday morning in the school field. The formulation of the problem in this research is how to design the literacy program at SDN 66 Jambi City, what are the supporting factors in its implementation, and the efforts made to overcome the obstacles in the program being run. This study uses a descriptive qualitative approach and data collection techniques, namely observation, interviews and literature. The results show that the school literacy movement program at SDN 66 Jambi City that has been implemented includes reading books, both story books and lessons that can increase students' interest, knowledge and insight, literacy facilities in the form of reading corners that already exist in several classes, so that they can create an environment that is rich in literacy even though it is still minimal.